Natural product-inspired synthesis of coumarin–chalcone hybrids as potential anti-breast cancer agents - Alhakamy, Nabil A.; Saquib, Mohammad; Sanobar,; Khan, Mohammad Faheem; Ansari, Waseem Ahmad; Arif, Deema O.; Irfan, Mohammad; Khan, Mohammad Imran; Hussain, Mohd Kamil (Frontiers in Pharmacology, 2023)
Twelve novel neo-tanshinlactone-chalcone hybrid molecules were constructed through a versatile methodology involving the Horner-Wadsworth-Emmons (HWE) olefination of 4-formyl-2Hbenzo[h]chromen-2-ones and phosphonic acid diethyl esters, as the key step, and evaluated for anticancer activity against a series of four breast cancer and related cell lines, viz. MCF-7 (ER +ve), MDA-MB-231 (ER-ve), HeLa (cervical cancer) and Ishikawa (endometrial cancer). The title compounds showed excellent to moderate in vitro anti-cancer activity, in a range of 6.8 to 19.2 µM (IC 50 ). Compound 30 (IC 50 = 6.8 µM, MCF-7; IC 50 = 8.5 µM, MDA-MB-231) and 31 (IC 50 = 14.4 µM, MCF-7; IC 50 = 15.7 µM, MDA-MB-231) exhibited the best activity with compound 30 showing more potent activity than the standard drug tamoxifen. Compound 30 demonstrated a strong binding This is a provisional file, not the final typeset article affinity with tumor necrosis factor α (TNF-α) in molecular docking studies. This is significant because TNFα is linked to MCF-7 cancer cell lines, and it enhances luminal breast cancer cell proliferation by upregulating aromatase. Additionally virtual ADMET studies confirmed that hybrid compounds 30 and 31 met Lipinski's rule, displayed high bioavailability, excellent oral absorption, favorable albumin interactions, strong penetration capabilities, and improved blood-brain barrier crossing. Based on the above results compound 30 had been identified as a potential anti-breast cancer lead molecule.